WAYS TO IMPROVE THE EFFECTIVENESS OF DIGITAL MARKETING STRATEGIES IN THE TOURISM SECTOR (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the context of current globalization and the development of digital technologies, the tourism industry has become in need of innovative approaches and modern marketing strategies. Digital marketing today is the most modern way to attract tourists, promote tourist services and products, strengthen the brand image, improve the efficiency of communication and make the most of modern information technologies. Especially marketing measures implemented through digital platforms today open up great opportunities not only for large companies, but also for representatives of small businesses and local tourist entities.